О дохлой кошке и живых котятах - Бутовская Марина (Другой, другие, о других, 2008)
Экземпляры: ДБ (20141118) / Инвентарный номер: 46187 / Цена: 150.00 / Авт.знак: Б 93 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6